Integrating metabolomics, genomics and disease pathways in age-related macular degeneration: The EYE-RISK Consortium - Acar, IE; Lores-Motta, L; Colijn, JM; Meester-Smoor, MA; Verzijden, T; Cougnard-Gregoire, A; Ajana, S; Merle, BMJ; de Breuk, A; Heesterbeek, TJ; van den Akker, E; Daha, MR; et al. (Elsevier, 2020)
Objective In the current study we aimed to identify metabolites associated with age-related macular degeneration (AMD) by performing the largest metabolome association analysis in AMD to date. In addition, we aimed to determine the effect of AMD-associated genetic variants on metabolite levels, and aimed to investigate associations between the identified metabolites and activity of the complement system, one of the main AMD-associated disease pathways. Design Case-control assocation analysis of metabolomics data. Subjects 2,267 AMD cases and 4,266 controls from five European cohorts. Methods Metabolomics was performed using a high-throughput H-NMR metabolomics platform, which allows the quantification of 146 metabolite measurements and 79 derivative values. Metabolome-AMD associations were studied using univariate logistic regression analyses. The effect of 52 AMD-associated genetic variants on the identified metabolites was investigated using linear regression. In addition, associations between the identified metabolites and activity of the complement pathway (defined by the C3d/C3 ratio) were investigated using linear regression. Main Outcome Measures Metabolites associated with AMD Results We identified 60 metabolites that were significantly associated with AMD, including increased levels of large and extra-large HDL subclasses and decreased levels of VLDL, amino acids and citrate. Out of 52 AMD-associated genetic variants, seven variants were significantly associated with 34 of the identified metabolites. The strongest associations were identified for genetic variants located in or near genes involved in lipid metabolism (ABCA1, CETP, APOE, LIPC) with metabolites belonging to the large and extra-large HDL subclasses. In addition, 57 out of 60 metabolites were significantly associated with complement activation levels, and these associations were independent of AMD status. Increased large and extra-large HDL levels and decreased VLDL and amino acid levels were associated with increased complement activation.